Development of Augmented Reality Flashcards as an Innovative Learning Media on Linear Motion - Khasana, Intan; Viyanti, Viyanti; Suyanto, Eko (Jurnal Pendidikan MIPA, 2023)
This research is a development research that uses the ADDIE Design Research and Development (R&D) model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The purpose of this study is to describe the validity and practicality. Augmented reality-assisted flashcards on linear motion material to increase students' learning interest. Product validity was assessed by 3 experts consisting of aspects of material and construct assessment as well as aspects of media and design assessment with an overall average score of 3.64 with a very valid category. The practicality of the product is assessed from the readability aspect and the teacher's perception aspect by obtaining an overall average percentage of 95% in the very practical category. Based on the analysis of the results of the data, it was concluded that the product resulting from the development of augmented reality-assisted flashcards on linear motion material was valid and practical to increase students' interest in learning.Keywords: flashcards, augmented reality, learning interest, linear motion.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp291-297